2020
DOI: 10.1111/cp.12198
|View full text |Cite
|
Sign up to set email alerts
|

“Guys don't talk about their bodies”: A qualitative investigation of male body dissatisfaction and sociocultural influences in a sample of 40 Australian males

Abstract: Background. Contemporary scholarship has established that increasing numbers of men are experiencing body dissatisfaction. However, as a consequence of the enduring assumption that body dissatisfaction is a feminine domain, male body dissatisfaction is associated with considerable stigma. Objective. The current study aimed to explore and describe men's experience with body dissatisfaction and investigate sociocultural influences in the context of male body image. Of particular interest was to obtain, from men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…It should be of note, however, that interest (i.e., behavioural engagement) was moderate among men, which may indicate less intent to engage with body image content more generally as body dissatisfaction and eating disorders are perceived to be feminine issues [ 61 ]. Reasons for this belief previously identified in research include lack of representation of men’s body dissatisfaction in media narratives [ 9 ], and masculine norms preventing men from discussing their dissatisfaction [ 9 , 62 , 63 ]. Future research could examine whether videos designed specifically with men in mind, using the same approaches used in the current study, may impact engagement differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be of note, however, that interest (i.e., behavioural engagement) was moderate among men, which may indicate less intent to engage with body image content more generally as body dissatisfaction and eating disorders are perceived to be feminine issues [ 61 ]. Reasons for this belief previously identified in research include lack of representation of men’s body dissatisfaction in media narratives [ 9 ], and masculine norms preventing men from discussing their dissatisfaction [ 9 , 62 , 63 ]. Future research could examine whether videos designed specifically with men in mind, using the same approaches used in the current study, may impact engagement differently.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a qualitative study identified that participants at an exercise facility had poor understanding of the construct of body image, and sometimes conflated a thinner appearance or weight loss with positive body image [ 8 ]. Similarly, poor understanding of the consequences of body dissatisfaction for men were identified among male participants [ 9 ]. As body dissatisfaction mental health literacy is generally low in the population, it is important that evidence-based, wide-reaching campaigns about this problem are available to facilitate appropriate treatment-seeking [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This attitude towards the male body is also discussed as the concept of Masculinity Ideology, and having a muscular body is considered as an indicator of "masculinity" O'gorman et al, 2020 Ridgeway and. Therefore, when evaluating body dissatisfaction in men, fear of losing weight or getting fat is mostly associated with the desire to have a muscular body, but not the desire to be thin (O'gorman et al, 2020;. In line with this, there is no gender difference in regard to body dissatisfaction, when the ideology of muscularity is added as a parameter in terms of body image .…”
Section: Beyanlarmentioning
confidence: 94%
“…Recent research suggests many young men experience body image dissatisfaction throughout their everyday lives, extending beyond muscularity and/or leanness, exemplified by growing concerns about appearance [ 26 , 27 ]. However, they may be reluctant to disclose these concerns [ 28 , 29 ] because to do so would be to lose ‘masculine capital’ [ 5 , 30 , 31 ]. Thus, while young men are expected to tacitly work towards attaining male (Western) body ideals, they must simultaneously appear indifferent to, or detached from, their bodily appearance, denoted as ‘the double-bind of masculinity’ [ 32 ].…”
Section: Introductionmentioning
confidence: 99%